ChemInform Abstract: Smart Chemistry in Polymeric Nanomedicine. Issue 50 (16th December 2014) - Tong, Rong; Tang, Li; Ma, Liang; Tu, Chunlai; Baumgartner, Ryan; Cheng, Jianjun
Abstract Review: overview of smart chemistry developed and utilized in the last 5—10 years in polymer‐based drug delivery nanomedicine; 506 refs.